Pendampingan Usaha Pemula untuk Peningkatan Kualitas Produk dan Promosi Digital di Desa Ladang Panjang: Penelitian - Hamdiah; Aegisia Sukmawati; Theressa Taken Pasaribu; Aninda Puji Adila; Naufal Kurniawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses mentoring activities for start-up businesses to improve product quality and digital promotion in Ladang Panjang Village. The program involved 15 start-up independent workers who received training on strategies for improving product quality and digital promotion through social media and marketplaces. The implementation method included workshops, intensive mentoring, and evaluation through pre- and post-tests. The results of the program showed a significant increase in participants' understanding of product quality and digital promotion strategies, including the ability to create promotional content, improve product packaging, and utilize digital media effectively. This mentoring is in line with findings (Hamdiah et al., 2025) that demonstrated the effectiveness of mentoring for start-up businesses in improving business planning, but this activity emphasized direct implementation on product quality and digital marketing. The results of this community service program indicate that practice-based mentoring and digital marketing can improve the performance of start-up businesses and support the economic independence of rural communities.